Nuclear quantum effect and temperature dependency on the hydrogen-bonded structure of 7-azaindole dimer - Nawee Kungwan (2018)
© 2014, Springer-Verlag Berlin Heidelberg. The structure of 7-azaindole dimer (7AI 2 ) as a model compound for DNA base pair has been studied by classical molecular dynamics (MD) and path integral molecular dynamics (PIMD) simulations on the semi-empirical PM6 potential energy surface at various temperatures, to investigate the nuclear quantum effect and temperature dependency on the hydrogen-bonded moiety of 7AI 2 . At 75 K, two H-bondings are maintained throughout a given simulation time in both classical and PIMD (quantum) simulations. At 150 K, these two H-bondings are maintained in only quantum simulation, while in classical simulation, the two H-bondings (or one H-bonding) are sometimes broken and reformed. For 225 K, these two H-bondings are broken in both classical and quantum simulations. We have also applied a principal component analysis to MD and PIMD simulations to analyze the intermolecular motions. We found that the ratio of the second lowest (dimer butterfly out-of-plane) vibrational mode from normal mode analysis which is the most dominant motion decreases with increasing temperature, whereas that of first lowest (dimer torsion out-of-plane) vibrational mode which is the second most dominant motion increases with increasing temperature from temperature 75 to 150 K and then decreases at 225 K due to the nuclear quantum effect. Moreover, the motions of two hydrogen-bonded structures are significantly different with increasing temperature. This difference is revealed by the principal component analysis which shows that the ratio of opening in-plane motion decreases and the ratio of stretching in-plane motion decreases.